PENDIDIKAN DI NEGARA-NEGARA ANGGOTA OKI: PERBANDINGAN ANTARA PEREMPUAN DAN LAKI-LAKI - Sari Lestari Zainal Ridho (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2010)
Education is the important aspect in human development. It is the tool for improving capacity building and capability of human resources. Human capital can be productive and more powerful through a good education. Although Islam support the quality and role of women but in many Islamic countries, unfortunately and empirically, there are still exist a discrimination toward women. It is not only exist in domestic issues, but also in education field. In those countries women education are still left behind of men education. Using data of educational condition at Organization of Islamic Conference (OIC) this article analyze that gap between men and women education at those countries still exist and become strategic issues or problems have to be solved by all of the OIC’s members.